Validity of Forex Trading Agreements Using Foreign Currency as the Object of Investment - Septianes Nora Kartika; Reka Dewantara; Faizin Sulistio (PT FORMOSA CENDEKIA GLOBAL, 2023)
Forex (Foreign Exchange) is better known in Indonesian as Forex trades between two currencies from two countries by many States Parties, institutions and individuals. Forex trading between market players that lasts Open 5 days a week, 24 hours a day. inner consistency Forex trading operations based on Article 1338 of the Legislative Code Civil. These provisions are less effective because there are still many brokers illegal brokers, unlicensed and unscrupulous companies with the intention of misleading investors. Due to the futures trading law Commodity has not yet implemented a complete forex trading system.Speaking of validity foreign exchange investment contract based on article 1320 of the civil code on the conditions of validity of the contract, foreign exchange as the object of the contract, not contrary to the objective conditions which have legal consequences, null and void history and characteristics of book iii of the civil code which regulates the commitment is open, so it is allowed to make one agreements other than those provided for in the civil code, provided that they are not contrary with the law, public order and good morals. This research advising the government and the legislator to make regulations related toforeign exchange investment regulations to prevent things that are not legal protection desired and guaranteed for investors